Unconventional Gas, Status and Perspectives for Its Exploration in Cuba - Orelvis Delgado López; Osvaldo López Corzo; Rafael Tenreyro Pérez; Juan Guillermo López Rivera (Revista Cubana de Ingeniería, 2013)
The purposes of this paper, is to define the unconventional gas types that can be found in Cuba andelaborate premises of perspectives areas for its exploration in Cuba. For this reason, a bibliographicrevision was done over the internet, because of the absent of textbooks and experiences of this topicin Cuba. For the enunciation of perspectives areas for unconventional gas exploration in Cuba, bothgas exploration reports in national territory and theoretical aspects elucidated over the internet wereused. Through this method of research it was possible to understand the theoretical aspect ofunconventional gas, the definition of the unconventional gas types that can be present in Cuba andthe most perspectives areas in order to begin its exploration. From these results it is possible toconclude that: The term unconventional gas is used because of the unconventional technical used formake the production of natural gas profitable from low quality reservoirs, and not because it is ahydrocarbon with different characteristics. The main unconventional gas types, which are beingdeveloped nowadays worldwide, are: Tight gas, shale gas y coal bed methane. Preliminarily, in Cubaonly exist conditions for tight and shale gas development.